(3GdGUWaG dHjGf eYGfj GdTaG ddbGVi YjGVs - (3TeS GdOjf eMeO Hf eMeO Hf CMeO GdOdLj GdTGaYjs; (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3YHOGdHGbi GdMfaj Hf eMeO GdeGOM GdefUhQj s)
(3ChdgG (B:s
(3fMeOc jG ef TQM UOhQfG HYdGeGJ TaGA deQVi GdCPgGf s
(3BNQgG (B:s
(3CfJ hdj aj GdOfjG hGdBNQI Jhafj eSdekG hCdMbfi HGdUGdMjf s
(3GdfSNI eLOhdI HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs